Association between college health services and contraceptive use among female students at five colleges in Wuhan, China: a cross-sectional study. (December 2016) - Long, Lu; Chen, Zhenhua; Shi, Yun; Wei, Sheng; Nie, Shaofa; Liu, Yi
Abstract Background College students have a high incidence of unplanned pregnancies in China, which has highly raised public attention. As such, numerous reproductive health services are provided to college students. This study examined whether health services in college lead to contraceptive use among female college students in heterosexual relationships. Methods A self-administered questionnaire survey with cross-sectional design was administered among female students in four colleges in Wuhan, China to identify health service factors associated with contraceptive use in the past 6 months. Results The analysis revealed that younger female students had lower odds of contraception use, whereas students who reported availability of health-related web sites were more likely to use contraceptives. Female students who reported that contraceptives and birth control counselling were accessible from college health services had greater odds of contraceptive usage. Finally, provision of contraceptives and birth control counselling from school were associated with greater odds of contraceptive use. Conclusions Contraceptive-related health services play an important role in reducing unintended pregnancies by directly addressing the contraceptive needs of female students. Programs that provide targeted services may help to reduce high rates of unexpected pregnancies among female students in China.